miR‐451a is downregulated and targets PSMB8 in prostate cancer - Yun Liu; Huan‐Zhi Yang; Yong‐Jun Jiang; Li‐Qi Xu (Kaohsiung Journal of Medical Sciences, 2020)
Abstract Abnormal expression of microRNAs (miRNAs) is frequently occurred in prostate cancer (PCa). This study was aimed to investigate the biological roles of miR‐451a in PCa. Quantitative real‐time PCR (qRT‐PCR) and Western blot were employed to investigate the expression levels of miR‐451a and proteasome (prosome, macropain) subunit, beta type, 8 (PSMB8) in PCa cell lines. Luciferase activity reporter assay was used to verify the connection between miR‐451a and PSMB8. in vitro functional experiments were performed to measure the effects of miR‐451a or PSMB8 on PCa cell proliferation, colony formation ability, cell invasion, and cell apoptosis. miR‐451a expression was downregulated, whereas PSMB8 expression was upregulated in PCa cell lines. Luciferase activity reporter assay confirmed the direct connection between miR‐451a and PSMB8. Overexpression of miR‐451a inhibits PCa cell proliferation, colony formation, cell invasion and promotes cell apoptosis, while the overexpression of PSMB8 caused the opposite effects. Moreover, rescue experiments confirmed PSMB8 was a functional target of miR‐451a. In conclusion, this study provides novel insights into the role of miR‐451a in PCa, and the results demonstrated miR‐451a could inhibit PCa progression by targeting PSMB8.